A qualitative study of men's recollections of growing up with father absence: childhood father figures and family resilience. Issue 4 (4th July 2017) - East, Leah; Hutchinson, Marie; Power, Tamara; Jackson, Debra
Abstract : Background : Families come in many forms and single parent women headed households are common with nurses being well positioned to provide support for these women and their children. For children growing up in lone parent households, the nature of family relationships and the availability of a social support network are important factors in reducing developmental risks. Aim : The aim of this study was to explore adult men's recollections of growing up in a father-absent home. Design : This study utilised a qualitative methodology. Methods : Semi-structured interviews were conducted with 21 adult men who grew up in a father-absent home due to family discord. Interview transcripts were thematically analysed using an inductive approach. Findings : Analysis of the interview transcripts revealed two themes relating to childhood father figures and family relational networks. For some men, ambivalent, violent or unavailable father figures stepped into the void created by the absent father. Others experienced positive father figures or multigenerational relationships, which provided positive relational supports and attachments. Conclusion : The findings illuminate the dynamics of family resilience and provide important insights for nurses and other family healthcare workers.